The - editor Carlos A.R. Sa de Melo
A collection of short review articles on the superconducting state in magnetic fields. The phiolosophy of the book is to emphasize the importance of having experimental and theoretical works side by side. The selection of materials includes special topics, effects and trends concerning superconductors in low and high magnetic fields. The special topics and new trends include: quantum and classical melting of the vortex lattice; new vortex lattice symmetries; vortex core states; nonlinear Meissner effect; symmetry of the order parameter in high-temperature superconductors; and superconductors in high magnetic fields